Brazilian Portuguese pronominal verbs: How to identify them? - Lenharo, Aline Camila [UNESP] (Springer Nature, 2015)
This paper shows the difficulties in delimiting Brazilian Portuguese Pronominal Verbs (BPPV) and proposes a way based on the theoretical assumptions of functionalism (especially the Dutch current) to formalize them, with a view to treatment of linguistic knowledge into computational-linguistic contexts. In this way, it aims, from a lexical-grammatical characterization of BPPV, to (i) systematize different subtypes of this verb type – such as: verb + SEpassive, verb + SEinherent, and verb + SEreflexive, identified from the different types of clitic SE; (ii) establish a comparison between various classifications checked for these verbal subtypes; and finally (iii) to establish a formal proposal to represent these different pronominal verbs subtypes based on Functionalism theoretical assumptions, with the objective of to addressing this linguistic knowledge into linguistic-computational contexts, such as the implementation/refinement of WordNet.Br verbs base. In this way, it is hoped to contribute with two complementary domains of research, the Linguistic Domain and the Linguistic-Computational Domain.
Keywords: Functionalist formal representation; Lexicogrammar; Pronominal verbs; Wordnets